EFECTO ALEPOPÁTICO DE TRES EXTRACTOS VEGETALES SOBRE EL DESARROLLO DE RAPHANUS SATIVUS (BRASSICACEAE) EN EL PERÚ - Ayala y Cols., Hildebrando (2019)
The use of plants with allelopathic activity nowadays is very important because it allows us to develop a profitable agriculture and non-polluting the environment. The objective of this work was to study the action of aqueous extracts of garlic (Allium sativum L, Liliaceae), avocado (Persea americana Mill, Lauraceae) and rough (Ruta graveolens L, Rutaceae) on the development of vegetable radish (Raphanus sativus L, Brassicaceae). The extracts were prepared from A. sativum bulbs, P. americana seeds and R. graveolens leaves and flowers to which he adds crushed boiled water. Treatments were the pure extracts (20% w / v). The design was completely randomized with 4 repetitions. It was found fresh weight (g), dry weight (g), root length (cm) long area (cm) and leaf area (cm2 ). The data was analyzed with Anova and Tukey test for the comparison of averages. The results show that there is no significant effects compared to the control of allelopathic potential of aqueous extracts tested under controlled conditions.